Algebra:







M= (x+5)2 – (x-5)2 +3 + 20x




N=(a+3)2 –(a-3)2
-10a




e= (x+2)2-(x-2)2-8x




a= (2a+b)2-(2a-b)2

2(2ab)




b=(x+3)2-(x-3)2


1
M = (x + 5 + (x - 5)) ((x + 5)-(x - 5)) + 3 + 20x = (2x)(10) + 3 + 20x = 40x + 3
N = ((a + 3) +(a - 3))((a + 3) - (a - 3)) - 10a = (2a)(6) - 10a = 12a - 10a = 2a
E = (x + 2)2 - (x - 2)2 - 8x = ((x + 2) + (x - 2)) ((x + 2) - (x - 2)) - 8x = 2x(4) - 8x = 8x - 8x = 0
A = ((2a + b)2 - (2a - b)2) / 2(2ab) = ((2a + b) + (2a - b) ((2a + b) - (2a - b)) / 4ab = (4a(2b)) / 4ab = 2
b= (x + 3)2 - (x - 3)2 = ((x + 3 + x - 3)(x + 3 - x + 3) = 2x(6) = 12x

Respuestas

2013-06-27T02:27:44+02:00
M=(2x+10)-(2x-10)+3 + 20
M= 2X+10-2X+10+3+20
M= 3